Transient splenial lesion of corpus callosum: A window to many diagnoses - Maqsood, Fathima Hana; Madhukeshwar, Adarsh Kibballi; Valiyapalathingal, Abdul Rasheed; U.S, Vinayaka; Acharya, Devadas; Gopalakrishna, Ravichandra (Asian Journal of Medical Sciences, 2021)
Transient splenial lesions (TSL) are not of frequent occurrence and are usually observed with other diseases. The mechanism of TSL development still unclear despite of various theories put forward. These are secondary lesions and their diagnosis is of importance to associate them with clinical conditions. Magnetic resonance imaging is the modality of diagnosing TSL and 3T MRI was used in this study. The study includes 10 cases of TSL with varied disease etiologies like migraine, trauma, infection, demyelination etc. All the cases had follow-up imaging which showed resolution of the lesions after varied time intervals. An attempt to correlate the various theories with each type of disease is done in this study.